Voter education package and KAP framework in electoral violence prevention among youth of voting-ages in Ondo City, Ondo State Nigeria - Timilehin Olayinka Omoniyi (Journal of Governance and Accountability Studies, 2026)
Purpose: This study aimed to assess the effectiveness of a voter education instructional package in improving the Knowledge, Attitudes, and Practices (KAP) framework for preventing electoral violence among youths in Ondo City, Nigeria. Methodology/approach: A quasi-experimental design with a pretest-posttest control group approach was adopted. The sample consisted of 183 youths of voting age, selected from four communities. The experimental group received a structured voter education package over eight weeks, while the control group was exposed to traditional instructional techniques. Data were collected using five validated questionnaires. ANCOVA was used for analysis. Results/findings: The study found that the treatment significantly improved participants' knowledge (F = 28.275, p < 0.05) and practice (F = 21.810, p < 0.05) regarding electoral violence prevention. However, there was no significant effect on attitude (F = 0.195, p > 0.05). Gender did not have a significant impact on any of the KAP components (p > 0.05). Conclusions: The voter education package significantly enhanced knowledge and practice among youths in Ondo City, making it a promising strategy for preventing electoral violence. However, it did not significantly change attitudes, suggesting that attitude transformation requires more extensive engagement. Limitations: The study focused on a specific region, and the sample size was limited to one state. Future studies should explore other regions and implement longitudinal assessments. Contribution: The study contributes to the field by offering an evidence-based voter education package that can be adopted in Nigeria and other developing democracies to mitigate electoral violence among youth.